A coupled numerical approach to simulate the effect of earthquake frequency content on seismic behavior of submarine tunnel. (January 2021) - Shekari, Mohammad Reza
Abstract: Roughly 90% of all natural vibrations have epicenters in offshore zones and may cause destruction of submarine and floating structures. Such excitations can influence the safe performance of facilities set up on the seabed, like tunnels, jacket legs and subsea oil pipelines. Some researches on this theme have been carried out to demonstrate the importance of seaquake analyses and their effects have been underlined. The present study intends to numerically simulate a two-dimensional fluid-structure interaction (FSI) problem in order to examine the dynamic response of submarine tunnel under real horizontal earthquakes. Pressure is considered as independent nodal variables to represent the fluid flow effects and the induced time-dependent acceleration in porous medium equation is incorporated in the analysis and the tunnel shell is considered as flexible. This work highlights the importance of the input ground motion frequency content that governs the development of the induced seismic stress/strain around the lining of the tunnel. The results demonstrate that for deep sea the increment rate of the circumferential stress caused by surface gravity waves is below 7% when compared to the no-wave interface condition. Moreover, it is confirmed that long-period record may amplify the overall response of the system (up to 60%) specially the lateral and vertical displacements, as well as the principal stress to a lesser extent. The developed numerical model can attend to further analysis of tunnels embedded in a half-space in conjunction with fluid undergoing the severe long-period earthquakes. Highlights: Time–dependent FEM of seawater–soil/rock mass–tunnel media was proposed. Circumferential displacements, accelerations and principal stress are analyzed. Broad new findings including some practical comments have been presented. It is shown that seismic performance of submarine tunnel is strictly sensitive to frequency content of the input motion.